Leliuk R.V. Analysis of power-social initiatives formation and development under current democratic reforms in Ukraine - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The preset paper considers formation of power-social initiatives under the conditions of current democratic reforms. The scienti c theoretical substantiation has been analyzed as regards establishing a relationship between public authorities and civil society institutions. Practical recommendations as to improvement of the relationship for the socio-economic development of the Ukrainian regions have been substantiated. A special attention is paid to analysis of the decentralization reform that has made a considerable contribution into development of power-social initiatives. Special features which should be taken into account when creating effective administration are discussed. Effective ways are proposed to develop the relationship between public authorities and civil society institutions in order to improve the present situation in Ukraine.